Numerical Modelling Based Investigation of Coal Pillar Stability for Room and Pillar Development at 900 m Depth of Cover - Ashok Kumar; Rajendra Singh; Petr Waclawik (International Conference on Ground Control in Mining, 2018)
High-grade coal is locked in the shaft protective pillars at 900 m below surface in the Czech part of Upper Silesian Coal Basin. To optimise recovery of coal from the larger size shaft protective pillar, room and pillar (called bord and pillar in India) is trialled to further develop these on smaller pillars. This development followed a constant gallery width of 5.2 m and 3.5 m height. The monitored pillar size in the first developed panel varied from 860 m2 to 1225 m2 of area. The stability of these pillars (i.e., natural supports) at this depth of cover is observed to be a vital issue to control ground movement and safety of the surface structures. A simple calculation of safety factor revealed that application of an empirical method for estimating size and shape of the pillar is inappropriate due to complex geo-mining conditions of the site. Accordingly, geo-technical instruments are installed in the panel for monitoring the stability of the diamond shaped pillar at different stages of the development. Extensive monitoring of the pillar behaviour by these instruments provided an important set of data for such optimum recovery. An established process of simulation-based pillar strength estimation is often used by the mining industry, but calibration is generally done with the help of empirical formulation. However, for the deep-seated pillar, the strength suggested by the existing empirical formulations (except the CMRI formula) is found to be much different from the instrument observations. Using a study conducted at Czech hard coal mines, an attempt is made to develop a strain-softening-based numerical modelling approach to assess pillar performance at deeper cover. The recorded value and nature of the pillar spalling in the field along with the CMRI formula are used to calibrate the developed simulation approach. An assessment of the stability of the developed pillars using simulated models did not indicate any collapse of the natural supports. This paper briefly presents difficulties in pillar design at great depth of cover and field and simulation results of pillar strength estimation in Czech hard coal mines.